Deciphering a Mystery: Digital Technology and the Revelation of Handwritten Texts by Marcel Nadjari and Other Members of the Jewish Sonderkommando in Auschwitz-Birkenau - Polian, Pavel; Nikitjaev, Alexander (East european Jewish affairs, 2019)
Jewish Sonderkommando's handwritten notes - found among the earth and ashes - are key documents of Holocaust history. But their degree of preservation is poor. Digital technology comes to the rescue to restore the legibility of these documents potentially lost to history. This article provides some examples of the successful application of image processing, which considerably increases the sharpness of the text. Special filters and approaches managed to increase by fourfold the number of pages from Marcel Nadjari's notes that could be read before. The deciphered fragments of Nadjari's notes not only allow us to better understand the meaning of the entire document, but also make a connection to another Nadjari text, thus yielding a new, much deeper, understanding of both the author himself, the particular fate of Greek Jews in the Holocaust, and also their role in the life and death of the Jewish Sonderkommando in Auschwitz-Birkenau.